2023
DOI: 10.3390/ijms24021588
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Cardiometabolic Risk: The Importance of the Risk Factors

Abstract: Metabolic syndrome (Mets) is a clinical condition characterized by a cluster of major risk factors for cardiovascular disease (CVD) and type 2 diabetes: proatherogenic dyslipidemia, elevated blood pressure, dysglycemia, and abdominal obesity. Each risk factor has an independent effect, but, when aggregated, they become synergistic, doubling the risk of developing cardiovascular diseases and causing a 1.5-fold increase in all-cause mortality. We will highlight gender differences in the epidemiology, etiology, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 166 publications
0
11
0
Order By: Relevance
“…The Atherosclerosis Risk in Communities study showed that metabolic disorders have higher levels of prognostic significance for CVD in women than in men, 48 a finding that is consistent with the greater impact of the components of metabolic syndrome in women than in men. 49 Thus, careful identification of sexspecific risk factors is not a mere formality but a vital cornerstone of full comprehension of atherosclerosis and cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The Atherosclerosis Risk in Communities study showed that metabolic disorders have higher levels of prognostic significance for CVD in women than in men, 48 a finding that is consistent with the greater impact of the components of metabolic syndrome in women than in men. 49 Thus, careful identification of sexspecific risk factors is not a mere formality but a vital cornerstone of full comprehension of atherosclerosis and cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes represents one of the most widespread conditions today, affecting ∼10% of the adult population of the United States 96 . Dysglycemia is central to the pathology of diabetes, resulting in a significant proportion of the morbidity and mortality associated with the illness 97, 98 . Treatment with APDs, some of the most widely prescribed psychiatric medications today, is a key contributor to the development of dysglycemia and T2D 99, 100 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that earlier age at menarche was associated with obesity and poor glycemic control in patients with type 2 diabetes [ 49 ]. Menopause transition and its incidental hormonal changes have also been associated with unfavorable changes in lipids, accumulation of abdominal adiposity, and increased blood glucose [ 50 ], and may contribute to the observed sex differences. Sex-related differences in lifestyle behaviors and psychological factors could also contribute to the sex difference in cardiovascular risk factor control.…”
Section: Discussionmentioning
confidence: 99%